ESTIMATION for THE FUNCTIONAL ACTIVITY of LIPO-OLIGOSACCHARIDE and N-ACETYL-D- GLUCOSAMINE on NODULATION of Medicago and Trifolium - N. Barhawi; M. Al- Mallah (Mesopotamia Journal of Agriculture)
In this study, Lipo-oligosaccharide (LOS) nod factor isolated from Sinorhizobium meliloti and Rhizobium trifolii SU157 were stimulated (two and three) nodules formationon the root of their specific plants, alfalfa (Medicago sativa) and white clover (Trifolium repens) respectively .This stimulation was clear on seedling grown on solid Nitrogen Free (NF) medium supplemented with (1.0 – 8.0 mg/L) Lipo-oligosaccharide . These nodules were small in size but became Larger with gradual increasing of LOS Concentration and increased in number on seedlings in inoculated with specific Rhizobium grown on solid NF medium supplemented with LOS from S.meliloti (11,10,11,12 Nodules/Plant) and R. trifolii (15,16,15,17 Nodules/Plant), comparing with grown on solid NF medium non- supplement with LOS molecule (8,13 Nodules/Plant). Where as the high concentration (8.0 mg/L) of rhizobial nod factor ;N-acetyl – D- glucosamine (GLcNAc) stimulated nodule formation on these Legume plants (1,2 Nodules/Plant).In contrast, these nod factors were unable, in the case of incompatable system , to form these nodules on the root of both clover and alfalfa seedlings. Light microscope study indicated that these nodules were empty and free from Rhizobium cells. Therefore this nod. factor are responsible for development of nodules on the host plant in the absence of rhizobial bacteria . The results of the statistical analysis by 3-way ANOVA of these values are significant at the level of potential alpha- 0.05 for alfalfa and clover plants.